PAHs formation simulation in the premixed laminar flames of TRF with alcohol addition using a semi-detailed combustion mechanism. (1st September 2015) - Jia, Guorui; Yao, Mingfa; Liu, Haifeng; Zhang, Peng; Chen, Beiling; Wei, Lixia
Highlights: Mole fraction of PAHs in the flames is in the order, n -butanol-TRF < ethanol-TRF < methanol-TRF < TRF. Concentrations of A1 and PAHs are mainly determined by the toluene content in the TRF. Additions of alcohols dilute toluene and thus reduce the formation of PAH. Slightly higher mole fractions of OH and O produced by alcohol additions will reinforce the oxidization of the PAHs. Abstract: Toluene reference fuel (TRF) is a kind of surrogate fuel for diesel. Clarifying the combustion mechanism of TRF is a key to understand the combustion of diesel. Alcohols are added into diesel to reduce the soot emission from engines. The formation mechanism of soot precursors, i.e., polyaromatic hydrocarbons (PAHs), in the premixed laminar flames of TRF, methanol-TRF blend, ethanol-TRF blend, and n- butanol-TRF blend were investigated experimentally and theoretically. A partly reduced n- butanol combustion mechanism, including the sub-mechanism of methanol and ethanol, and a partly reduced soot formation mechanism were merged into a partly reduced mechanism of TRF to simulate the combustion of the TRF-alcohol blends. Additions of methanol, ethanol, and n- butanol can reduce the mole fractions of the PAHs in TRF flames at an equivalence ratio of 2.0. The mole fractions of the PAHs in the flames are in the order of n- butanol-TRF < ethanol-TRF < methanol-TRF (<TRF) at a fixed oxygen content of 4.0%. The simulation results show that benzene is overwhelmingly produced from the toluene in TRF. Additions of the alcohols into TRF have negligible effect on the branching ratios of toluene consumption, but may increase the mole fractions of OH and O, which accelerate the oxidation of PAHs formed in the flames, at the fixed oxygen content of 4.0%. The decrease of PAHs can be attributed to the effect of dilution by the additions of the alcohols.